Aortic arch branch-prioritized reconstruction for type A aortic dissection surgery - Gao, Jianfeng; Yan, Jie; Duan, Yanyu; Yu, Junjian; Li, Wentong; Luo, Zhifang; Yu, Wenbo; Xie, Dilin; Liu, Ziyou; Xiong, Jianxian (Frontiers in Cardiovascular Medicine, 2024)
Background Acute Stanford type A aortic dissection (STAAD) is a fatal condition requiring urgent surgical intervention. Owing to the complexity of the surgical process, various complications, such as neurological disorders, are common. In this study, we prioritized the reconstruction of aortic arch branches during surgery and investigated the association between prioritizing the branches and the postoperative outcomes of patients with STAAD. Methods Ninety-seven patients were included in the observational study and underwent total arch replacement and frozen elephant trunk technique between January 2018 and June 2021. Of these, 35 patients underwent the branch-priority technique, and 62 patients underwent the classic technique. By analyzing the perioperative outcomes, we compared the differences between the two techniques. Results The branch priority group had significantly shorter cardiopulmonary bypass and ventilator times and earlier postoperative wake-up times than the classic group. Additionally, the ICU stay time was shorter, with a significant decrease in neurological complications and 24 h drainage in the branch priority group compared to the classic group. Conclusion The branch priority technique can effectively provide better brain protection, resulting in earlier awakening of patients after surgery, reduced neurological complications, shorter ventilation time and decreased ICU hospitalization time. Therefore, it is recommended for use in aortic dissection surgeries.